Educación inclusiva en estudiantes de cuarto grado de secundaria en instituciones educativas según tipo de gestión del distrito de Iquitos 2021 - Huani Torres, Rina Marcela (2023)
The objective of this study was to compare fourth year students’ inclusive education between public and private secondary schools in Iquitos district 2021. The research type was comparative with field study, transactional contemporary and univariate designs. The study population was made up by 2884 students and a stratified sample with proportional allocation of 395. The test results showed that the mean score of public-school students was a little bit higher than those of private schools (61,420 > 61,179), as well as in their dimension: elaboration of inclusive politics (59,69 > 58,09), but in dimensions: inclusive culture creation (61,49 < 62,91), inclusive values (56,59 < 56,91) and inclusive practice (56,28 < 56,65), showed that the mean scores of privateschool students were a little bit higher than those of public school. In conclusion, the U test of Mann-Whitney for independent samples showed that there are no significant differences in inclusive education between public and private school students as pvalue = 0,491 > = 0.05, rejecting the working hypothesis.